1984
DOI: 10.1007/bf01963592
|View full text |Cite
|
Sign up to set email alerts
|

Influence of posttreatment temperature on the toxicity of pyrethroid insecticides to susceptible and resistant larvae of the Egyptian cotton leafworm,Spodoptera littoralis (Boisd.)

Abstract: 188blocking effect directly on the muscle. This effect is significantly inferior to the inhibitory effect observed when the muscle is stimulated via the nerve. These observations suggest that the target for these compounds is to be found in the nerve muscle junction. The effect of the analogues III and IV on the twitch tensions is of the same order of magnitude as demonstrated for I and II. It is therefore suggested that the mode of action of HI might correspond to that of I and II. The mode of action of IV se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…A similar mechanism was proposed for the observed inverse temperature effect on pyrethroid toxicity to a leafworm, Spodoptean littoralis [37], and a temperaturedependent change in pyrethroid metabolism has also been seen in rainbow trout [35]. Chironomus dilutus readily biotransformed permethrin at both temperatures, however, the biotransformation rate (k m ) at 13ЊC was half that at 23ЊC.…”
Section: Mechanistic Considerationssupporting
confidence: 60%
“…A similar mechanism was proposed for the observed inverse temperature effect on pyrethroid toxicity to a leafworm, Spodoptean littoralis [37], and a temperaturedependent change in pyrethroid metabolism has also been seen in rainbow trout [35]. Chironomus dilutus readily biotransformed permethrin at both temperatures, however, the biotransformation rate (k m ) at 13ЊC was half that at 23ЊC.…”
Section: Mechanistic Considerationssupporting
confidence: 60%
“…Johnson (1990) has shown that deltamethrin is more effective at higher body temperatures in two species of grasshoppers, Camnula pellucida (Scudder) and Melanophus bivittatus (Say), but this relationship may be reversed in other species (e.g. Riskallah, 1984;Grafius, 1986). However, since the selected body temperatures of the two lizards species that we investigated differ by less than 13C (Huey et al, 1977), it is unlikely that temperature difference is the main cause of the difference in the decrease in abundance.…”
Section: Discussionmentioning
confidence: 71%
“…This implies that metabolic detoxification by monooxygenases, esterases and glutathione/glutathione S ‐transferases may all be involved in imparting chlorpyrifos resistance. Chlorpyrifos was synergized by both PBO and DEF in S littoralis 39 and DEF increased the toxicity of chlorpyrifos in H virescens , explaining its tolerance 40. Increased levels of monooxygenase activity as well as increased hydrolysis of chlorpyrifos oxon were mainly responsible for resistance to chlorpyrifos in B germanica 41.…”
Section: Resultsmentioning
confidence: 99%